(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amalia R, Rejeki S, Widowati LL, Ariyati RW. 2021. The growth of tiger shrimp (Penaeus monodon) and its dynamics of water quality in integrated culture. Biodiversitas 23: 593-600. Intensive shrimp culture with high density will have an impact on environmental problems. One of them is the accumulation of organic materials. Integrated Multi-trophic Aquaculture (IMTA) is an alternative effort to reduce the environmental impact of aquaculture activities, which can help maintain the balance of the ecosystem. Seaweed and shellfish in the culture system can improve environmental quality. Therefore, it can assist in optimizing friendly environmental shrimp culture. This study aimed to find out the growth of tiger shrimp and the role of seaweed and blood cockles and its dynamics of water quality. Twelve fiberglass tanks containing 800 L of brackish water and filled with ± 10 cm of clay sediment were arranged randomly. This study used 4 treatments and 3 replications, including treatment A (tiger shrimp), B (tiger shrimp+seaweed), C (tiger shrimp+blood cockle), and D (tiger shrimp+seaweed+blood cockle). The data of tiger shrimp growth was monitored weekly, while the growth of blood cockle and seaweed was collected at the end of the study. The water quality parameters such as DO, pH, temperature, and salinity were monitored daily. Meanwhile, the data of Total organic matter (TOM), total ammonia nitrogen (TAN), NO2, and NO3 were measured weekly. The result of the research showed that the highest specific growth rate (SGR) was treatment D (5.75±0.03% day-1). While the highest SR value was treatment B 90.33±0.58%. However, survival rate (SR) on treatment B did not have a significant difference (p<0.05) with treatment C and D. In general, there was significant interaction (p<0.01) in organic waste parameters (TOM, TAN, NO2, and NO3) for all treatments. In removal rate (RR), treatment D was more effective in reducing TOM (19,20%). Meanwhile, the highest level of TAN reduction was achieved by treatment C (50%). In addition, the highest reduction in nitrite and nitrate variables was in treatment D (40% and 33,33%). In contrast, treatment A got a negative removal rate in all parameters.